2014
DOI: 10.1080/09687599.2014.982788
|View full text |Cite|
|
Sign up to set email alerts
|

Inclusion, integration, or what? A comparative study of the school principals’ perceptions of inclusive and special education in Finland and in Alberta, Canada

Abstract: This study explores the perceptions of school principals in terms of organizing inclusive and special education in two well-performing, western school systems in Finland and in Alberta, Canada. The interview data reveal that, in spite of the inclusive rhetoric within education policy documents, most of the principals were still defining their current practices using the language of integration, and the educational decisions were often based on the more traditional idea of the least restrictive environment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 22 publications
1
35
0
11
Order By: Relevance
“…The dilemma related to placement of pupils with SEN has also been described in previous studies (e.g. Jahnukainen 2015;Norwich 2008). This dilemma could indicate that, in many schools, arrangements for providing support in mainstream groups are not yet at the same level as those for special groups.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The dilemma related to placement of pupils with SEN has also been described in previous studies (e.g. Jahnukainen 2015;Norwich 2008). This dilemma could indicate that, in many schools, arrangements for providing support in mainstream groups are not yet at the same level as those for special groups.…”
Section: Discussionsupporting
confidence: 52%
“…Graham and Sweller 2011;Kirjavainen, Pulkkinen and Jahnukainen 2014b) have found that segregated placements have not decreased; instead, the increase of pupils with SEN in general education classrooms has resulted from the overall growth in the identification of pupils with SEN. Available resources and supports are considered when professionals decide whether to place a pupil with SEN in a general education classroom (Jahnukainen 2015). Norwich (2008) has demonstrated that professionals recognise the dilemma involved in the placement of pupils with SEN (reduced specialist provision or exclusion) and seek to balance inclusion and separate provision to resolve this dilemma.…”
Section: Inclusion and Funding Of Special Educationmentioning
confidence: 99%
“…The students in our study refused to transfer to GE-classes for reasons school personnel misunderstood or simply ignored. Regardless of the inclusive tone in Finnish education policies and legislation we found that in practice the idea of integration and exclusion are maintained (Mietola, 2014;Jahnukainen, 2015). Distinctive practices,…”
Section: Discussionmentioning
confidence: 92%
“…) However, as international research shows, inclusion can become an empty policy buzzword devoid of meaningful challenges to opposing educational practices (Armstrong, 2005;Youdell, 2006;Oliver and Barnes, 2010). While the policy has shifted from segregated to inclusive education within Finnish special education, general schoollevel educational practices are still often based on integration (Mietola, 2014;Jahnukainen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the alignment of policies and laws with international standards has led to inclusion, different countries may use the same educational policy differently (Maclean 2017;Miškolci et al 2016). While a shared understanding about inclusive education is available at a theoretical level, several political and policy adoption realities have an impact at the operational level subjective to different educational contexts (Jahnukainen 2015). Hence, this paper has focused on practical approaches to addressing racial inclusion, predominantly in the context of Australian education.…”
Section: Education System Framework To Address Racismmentioning
confidence: 99%